A two-way loose coupling procedure for investigating the buckling and damage behaviour of stiffened composite panels. (February 2016) - Hühne, Sina; Reinoso, José; Jansen, Eelco; Rolfes, Raimund
Abstract: This paper is concerned with the development of a novel FE-based two-way loose coupling approach for the analysis of stiffened composite panels. The aim of this numerical strategy is to investigate the global postbuckling behaviour as well as the local damage progression of composite structures using separated FE models with different levels of fidelity: (i) a relatively simple global model of the complete structure, and (ii) more complex local models of certain details that incorporate damage capabilities to simulate damage events. In the coupling process, information is exchanged between these diverse models to simulate the overall structural behaviour including geometrical as well as material nonlinearities. The two-way loose coupling character of the methodology allows, firstly, a direct interaction between the global and the local levels along the solution process and, secondly, a highly versatile adaption with regard to the definition of the local models. In addition, the separation of the models and analyses in the approach enables the use of standard FE software without complex implementations or modifications of the source code. The developed coupling procedure is assessed through two applications: (i) an academic composite stiffened panel, and (ii) a real stiffened panel taken from literature. The results of the proposed coupling approach are compared with the numerical and experimental reference data, exhibiting a satisfactory level of accuracy.